Comparative study of the feeding damage caused by the South African biotypes of the Russian wheat aphid (Diuraphis noxia Kurdjumov) on resistant and non-resistant lines of barley (Hordeum vulgare L.) - Jimoh, Mahboob Adekilekun (Rhodes University, Faculty of Science, Botany Department, 2011)
Cereal crop productivity is hampered when these plants are infested by phloem feeding aphids. A great deal of research has been carried out with the direct aim of a clearer understanding of the mechanism involved in the interaction between aphids and their host plants. Research has directly or indirectly been geared towards enhanced plant productivity and achieving sustainable agriculture. Barley (Hordeum vulgare L.) is an important small grain crop in South Africa, whose crop performance is negatively affected by fluctuations in weather patterns as well as by agricultural pests. One of the insect pests infesting barley is the Russian wheat aphid, Diuraphis noxia Kurdjumov (RWA), of which the two South African biotypes, codenamed RWASA1 and RWASA2, were studied in this thesis. During dry spells, RWA infestation becomes a more serious threat to barley productivity. Resistant plants have been used to combat RWA infestation of small grains. In South Africa, 27 RWA-resistant wheat cultivars are currently used in commercial cultivation, but no resistant barley lines have, unfortunately, been developed, in spite of this grain's significant economic importance. This informed the study in this thesis, and this interest particularly focussed on three RWA-resistant lines developed by the USDA, testing their performance against South African RWA biotypes, for possible adaptation to South Africa. The aim was thus to examine the plant-aphid interactions, aphid breeding rates, plant damage and sustainability, evidence of resistance or tolerance and finally potential performance under elevated CO2 (a very real climate change threat). Two major avenues of research were undertaken. The first aspect involved examination of structural and functional damage caused by RWASA1 and RWASA2 on the three resistant and a non-resistant line. Aphid population growth and damage symptoms (chlorosis and leaf roll) of infestation by these aphid biotypes were evaluated. This was followed by a structural and functional approach in which the effects of feeding on the transport systems (phloem and xylem) of barley were investigated. Fluorescence microscopy techniques (using aniline blue fluorochrome, a specific stain for callose and 5,6-CFDA, a phloem-mobile probe) were applied to investigate the feeding-related damage caused by the aphids, through an examination of wound callose formation and related to this, the resultant reduction in phloem transport capacity. Transmission electron microscopy (TEM) techniques provided evidence of the extent of the feeding-related cell damage. The second aspect involved a study of the effect of changing CO2 concentrations ([CO2]) on the resistant and susceptible barley cultivars to feeding by the two RWA biotypes. Leaves of plants grown at ambient and two elevated levels of [CO2] were analysed to investigate the effect of changing [CO2] on biomass, leaf nitrogen content and C:N ratio of control (uninfested) and infested plants. The population growth studies showed that the populations of the two RWA biotypes as well as bird cherry-oat aphid (BCA, Rhopalosiphum padi L.) increased substantially on the four barley lines. BCA was included here, as it had been the subject of several previous studies. RWASA2 bred faster than RWASA1 on all lines. The breeding rates of the two RWA biotypes were both suppressed and at near-equivalent levels on the three resistant lines, compared to the non-resistant PUMA. This suggests that the resistant lines possessed an antibiosis resistance mechanism against the feeding aphids. Feeding by the aphids manifested in morphological damage symptoms of chlorosis and leaf roll. The two biotypes inflicted severe chlorosis and leaf roll on the non-resistant PUMA. In the resistant plants, leaf rolling was more severe because of RWASA2 feeding compared to RWASA1 feeding. In contrast, chlorosis symptoms were more severe during RWASA1 feeding than was the case with RWASA2 feeding. Investigation of the effect of aphid feeding on the plants showed that callose was deposited within 24h and that this increased with longer feeding exposure. Wound callose distribution is more extensive in the non-resistant PUMA than in the resistant plants. RWASA2 feeding on the resistant lines caused deposition of more callose than was evident with RWASA1 feeding. During long-term feeding, it was evident that variation in the intensity and amount of wound callose was visible in the longitudinal and transverse veins of the resistant plants. Of the three STARS plants, STARS-9301B had the least callose. Interestingly, wound callose occurred in both resistant and non-resistant plants, in sharp contrast to what has been reported on resistant wheat cultivars that were developed in South Africa. The relative reduction in the wound callose deposited in the resistant line, when compared to the non-resistant lines, suggests the presence of a mechanism in the resistant lines, which may prevent excessive callose formation. Alternatively, the mechanism may stimulate callose breakdown. RWASA2 feeding on the resistant lines deposited more wound callose than RWASA1 feeding. This evidence supports the hypothesis that RWASA2 is a resistance breaking and more aggressive feeder than RWASA1 is; and further underscores the urgent need for development of RWA-resistant barley cultivars. The ultrastructural investigation of the feeding damage showed that the two biotypes caused extensive vascular damage in non-resistant plants. There was extensive and severe cell disruption and often obliteration of cell structure of the vascular parenchyma, xylem and phloem elements. In sharp contrast, among the resistant plants, feeding-related cell damage appeared to be substantially reduced compared to the non-resistant PUMA. Low frequency of damaged cells indicated that majority of the cell components of the vascular tissues were intact and presumed functional. There was evidence of salivary material lining the secondary walls of the vascular tissue, which resulted in severe damage. Within xylem vessels, saliva material impregnated half-bordered pit pairs between the vessels and adjacent xylem parenchyma. This is believed to prevent solute exchange through this interface, thereby inducing leaf stress and vi leaf roll. A notable finding is that RWASA2 effectively induced more cell damage to vascular tissues in the resistant lines than did RWASA1. In general the experimental evidence (see Chapter 5) suggests that the resistant lines are possibly more tolerant (or able to cope with) to RWA feeding. Evidence for this is the reduction of wound callose and at the TEM level, a comparatively less obvious cell damage in the resistant lines, which suggests that they possess antibiosis and tolerance capacity. The apparent reduction of feeding-related cell damage from the TEM study confirmed the disruptive action of the feeding aphids in experiments using the phloem-mobile probe, 5,6-CF. Results showed that feeding by RWASA1 and RWASA2 reducedthe transport functionality of the phloem in all cases, but that RWASA2 feeding caused a more obvious reduction in the rate and distance that 5,6-carboxyfluorescein was transported, than did RWASA1. Investigation of the effect of changing [CO2] on the barley cultivars showed that in the absence of aphids and under elevated CO2 conditions, the plants grew more vigorously. In this series of experiments, the infested plants suffered significant reduction in biomass under ambient (as was expected) and under the two elevated CO2 regimes. Biomass loss was greater at elevated CO2 than under ambient [CO2]. The infested nonresistant PUMA plants showed a more significant biomass loss than did the resistant cultivars. Clearly, the benefits derived from elevated CO2 enrichment was thus redirected to the now-advantaged aphids. Uninfested vii plants showed an increase in leaf nitrogen under the experimental conditions. However, feeding aphids depleted leaf nitrogen content and this was more apparent on plants exposed to RWASA2 than was the case with RWASA1. The end result of this was that C:N ratio of infested plants were higher than uninfested plants. Clearly, the faster breeding rates of the aphids at elevated CO2 caused depletion of N and a resultant deficiency exacerbated chlorosis as well as leaf rolling due to the higher aphid population density under elevated CO2 than at ambient. By 28 days after infestation (DAI), majority of the plants exposed to enriched CO2 treatments had died. A major finding here was thus that although this study demonstrated that elevated CO2 resulted in an increase in biomass, this was detrimentally offset in plants infested by the aphids, with a decline in biomass and loss of functionality leading to plant death at 28DAI. The overriding conclusion from this study is a clear signal that the twin effects of CO2 enrichment (a feature of current climate change) and aphid infestations may precipitate potential grain shortages. A disastrous food security threat looms.
Keywords: Aphids; Russian wheat aphid -- Research -- South Africa; Barley -- Diseases and pests -- South Africa